TRIANGLE CONCEPT CONSTRUCTION THROUGH ETHNOMATHEMATICS-BASED ONLINE LEARNING OF KALAMATA FORT ARTIFACTS - Pakaya, Yusril M; Marsigit, Marsigit (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2023)
This study aimed to construct a triangle for junior high school students through online learning based on the Ethnomathematics of Kalamata Fort Artifacts. This research is descriptive qualitative research with a case study type. The data collection methods used are concept understanding tests and interviews. The subjects of this study were three students who were grade VII junior high school students with high (S1), medium (S2), and low (S3) abilities. In this study, the data analysis conducted was descriptive. The data analyzed in this study are the results of concept understanding observations and interviews conducted by researchers on research subjects. The results showed that constructing the concept of triangles through online learning based on the Ethnomathematics of Kalamata Fort Artifacts had a good impact on the concept understanding ability of grade VII junior high school students.